PENGARUH PROFITABILITAS, KEPUTUSAN PENDANAAN, KEPUTUSAN INVESTASI DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Nani Hartati; Fajar Fitriyani (Unitri Press, 2020)
The company's value (Tobins'Q) is influenced by Return On Equity(ROE), Debt to Equity Ratio(DER), Market to book value of equity (MBVE) and Dividend Payout Ratio (DPR). This research is intended to look at the influence of ROE, DER, MBVE and DPR on Tobins'Q. This type of research explanatory uses quantitative methods in which the population of Consumer Goods Industry registered in IDX in 2014-2018. Purposive sample is a method in sample selection where there are 17 companies as samples. Multiple linear analysis is used in analyzing data with a signification rate of 5% and data processing using Eviews 10, partially ROE and DPR has a positive and insignificant direction to the company's value, DER is negative and significant to the value of the company, MBVE has a positive direction and has a significant effect on the value of the company. Simultaneously ROE, DER, MBVE and DPR together affect the value of the company. Profitability, funding decisions, investment decisions and dividend policy increased the value of the company by 86.67% while the 13.33% was due to factors beyond the research variable.